An assessment of the trends in international price competitiveness among EMU countries - Christoph Fischer (Deutsche Bundesbank, 2007)
Inflation differentials within European Monetary Union (EMU) are increasingly seen as exerting adverse effects on the price competitiveness of member countries' firms and – given the common monetary policy within EMU – as being detrimental to euro-area economies, in particular to those with relatively high inflation rates. Using three simple measures of international price competitiveness for EMU countries, the paper analyses whether these indicators have displayed distinctive trends since the start of EMU and whether they converge with or diverge from their respective fundamental value. It is found that all three indicators suggest a gain in competitiveness for the German economy and a corresponding loss for Italy, Portugal and Spain. Two of the indicators, however, suggest that these trends reduce former disparities and, thus, contribute to a convergence of competitiveness within EMU while the third would imply the opposite.
Keywords: E31; F36; F31; 330; Price competitiveness; EMU; purchasing power parity; productivity approach; panel unit root tests; panel cointegration; Preiswettbewerb; Internationaler Wettbewerb; Kaufkraftparität; Entwicklungskonvergenz; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Staaten